A STUDY OF THE DEMONSTRATIVES IN ENGLISH vs VIETNAMESE - Ph. D TRAN QUANG HAI (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This study aims at investigating English and Vietnamese demonstratives in terms of syntax, semantics and pragmatics. Hopefully that this study will be of use to not only English teachers and learners but also those who have something to do with language learning and language teaching in general.